Self-Actualization In William Somerset Maugham's Of Human Bondage: Humanistic Psychological Approach - Munfarida, Munfarida (2005)
The problem of this study is how the major character, Philip Carey actualizes himself in William Somerset Maugham's Of Human Bondage. The objective of this study is to analize William Somerset Maugham's Of Human Bondage based on the structural element and Maslow's humanistic psychological approach. This study belongs to qualitative research. In this method, there are two types data sources which are used, namely primary and secondary data sources. The primary data source is the novel itself. The secondary data source is taken from books and other sources which support the analysis. The method of data collection is library research and tecnique of data collection is descriptive technique. Having analyzed the novel, the writer draws that Plilip Carey, the major character of the novel can actualize himself although he is cripple. It can be known from his life that he can pass the four basic needs (Physiological needs, Safety needs, Love and Belongingness needs, Self esteem needs) and has the fifteen characteristics of Selfactualization.